2016
DOI: 10.5546/aap.2016.eng.209
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on human immuno deficiency virus mechanisms of transmission among schoolchildren in the age range of 11 to 20 years old from poor districts of Bucaramanga, Colombia

Abstract: Introduction.Human immunodeficiency virus (HIV) infection was the second most common cause of death, after injuries of external causes, among young adults from Bucaramanga in 2013. Objective. To establish the extent of knowledge on HIV mechanisms of transmission prevention strategies among schoolchildren in the age range of 13 to 20 years old from poor districts of Bucaramanga. Methodology. Cross-sectional study among randomly selected schoolchildren using a selfadministered anonymous survey. For analysis, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In the present study, the level of knowledge of HIV and other STIs was medium to low; important gaps were observed regarding forms of transmission and general prevention. Other studies, focused on Colombian adolescents [17, 29] and Spaniard adolescents [26, 34], have reported similar results. This situation highlights the need to modify erroneous sexual beliefs and to provide reliable information to adolescents.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the present study, the level of knowledge of HIV and other STIs was medium to low; important gaps were observed regarding forms of transmission and general prevention. Other studies, focused on Colombian adolescents [17, 29] and Spaniard adolescents [26, 34], have reported similar results. This situation highlights the need to modify erroneous sexual beliefs and to provide reliable information to adolescents.…”
Section: Discussionsupporting
confidence: 70%
“…The prevalence of unprotected sex was revealed to be as high as 70% in a study with Colombian young people between 15 and 24 over the 12-month period before the study [16]. Becoming sexually active before 15, having low condom use intentions, and inadequate knowledge about STIs and protection methods are risk factors for lack of condom use identified for Colombian adolescent populations [6, 16, 17]. In a cohort study focused on students between 13 and 21 [6], investigators found that 60% of the students had become sexually active before 15 years of age, 58% failed to use condoms, and 39% had insufficient knowledge on sexual health.…”
Section: Introductionmentioning
confidence: 99%